Breakthroughs on the clinical management of headache and questions that need to be solved. Issue 4 (9th December 2021) - Liu, Yu‐Cong; Yang, Ting‐Ting; Li, Jing; Xu, Hui‐Chan; Li, Shun‐Lian; Xiong, Liu‐Lin
Abstract: Headache is a common refractory disorder among adults, especially in females, which can lower the quality of life in patients and increase medical costs. Nearly 90% of people have been affected by headache disorders during their lifetime. The severe situation of headaches has drawn the attention of researchers in recent years. Although the mechanism of headache has not been fully understood by us, there are many effective preventive drugs and treatments available. This review is aimed to sum up the progress in clinical trials of headaches in the past 5 years. Abstract : Studies on headaches had flourished over the past 5 years, tons of advances had been made. In the treatment of headaches, the approval of the Lasmiditan brought a second spring of the traditional 5‐HT agonists' drugs. Also, the efficacy of novel treatments like CGRP drugs and BTA has been proved by multiple RCTs, so did the nonpharmacological treatment. For the mechanism of the headache, besides the agreed‐upon trigeminovascular pathways, recent studies revealed that the K‐ATP channel and five types of miRNAs may play a crucial role in the pathogenesis of headaches. Moreover, hypoxia and the level of glutamate have been certified to be the triggers of headaches. Nevertheless, our understandings of the mechanism of headache are still incomplete. In this review, we summarized studies on headaches in the past 5 years to help researchers get to the newest progress in the field of headaches.